A Hybrid Approach of AES and File Encryption to Enhance The Cloud Security (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Cloud computing is a paradigm shift in the way we define software and hardware, and architect our IT solutions. The emerging cloud technologies, due to their various unique and attractive properties, are evolving with tremendous momentum and rapidly being adopted throughout the IT industry. In this dissertation, we identify security challenges that arise in integration of cloud-based services, and present a set of novel solutions to address them. We analyze the security of our solutions, demonstrate their usage and effectiveness, and evaluate their performance by extensive experimentation. To address the problem of security in untrusted cloud storage, we introduce a hybrid solution of AES and file encryption. The key used in AES algorithm is generated randomly from the file's data which is sent by the cloud provider. After implementing the proposed methodology, we have seen an improvement in the processing time and cost which will increase the overall efficiency of the system.Â